2016
DOI: 10.1186/s40038-016-0011-4
|View full text |Cite
|
Sign up to set email alerts
|

The science behind the development and performance of reduced ignition propensity cigarettes

Abstract: A burning cigarette is a known cause of fire when mishandled. Studies into cigarette ignition propensity intensified after the US Cigarette Fire Safety Act of 1984. Extensive research has investigated the thermal properties of a smouldering cigarette, mostly away from any object of thermal contact or interference. To understand fire ignition, the thermophysics of cigarette's burning tip has also been examined with and without a contact substrate. In either free or contact smouldering cases, oxygen diffusion th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 94 publications
(100 reference statements)
1
9
0
Order By: Relevance
“…Our results reinforce the mixed state of the evidence regarding the effects of fire safe cigarette laws,6 and despite finding an indication of an effect on cigarette-related fire mortality rates, we are still left with some unanswered questions. For instance, why would cigarette-related deaths have been affected while the cigarette-related fires in general have remained unchanged?…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Our results reinforce the mixed state of the evidence regarding the effects of fire safe cigarette laws,6 and despite finding an indication of an effect on cigarette-related fire mortality rates, we are still left with some unanswered questions. For instance, why would cigarette-related deaths have been affected while the cigarette-related fires in general have remained unchanged?…”
Section: Discussionsupporting
confidence: 72%
“…However, the empirical evidence on the effects of these laws on the occurrence of fires and fire mortality paints a mixed picture, with effect sizes ranging from −40% to null effects 6. Most of these studies are based on case studies of countries or subnational jurisdictions,7–10 which may be problematic due to the possibility of publication bias in favour of statistically significant results in the expected direction 11.…”
Section: Introductionmentioning
confidence: 99%
“…Baker and his colleagues reported that findings from several studies on the effectiveness of these requirements ranged from a 40% reduction in fires started by smoking materials compared to the period before implementation to no observable effect. They also noted that “The test method in the ASTM E2187 standard represents a simplified fire initiation scenario as compared with the multitude of possibilities of real‐life fire initiation.” 32 …”
Section: Discussionmentioning
confidence: 99%
“…Globally, fires are a common cause of emotional distress, physical injury and death, and studies show that residential fires are a major cause of fire-related morbidity and mortality [1]. One of the main risk factors for residential fires is dropped or improperly discarded cigarettes [2]. These types of fires are usually caused by smokers falling asleep with a lit cigarette or dropping their cigarettes or discarding them negligently [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%